Cardiac tamponade and adrenal insufficiency due to pembrolizumab: a case report. Issue 2 (3rd April 2018) - Oristrell, Gerard; Bañeras, Jordi; Ros, Javier; Muñoz, Eva
Abstract: Introduction: Patients who receive or have received anti-programmed cell-death-1 (PD-1) monoclonal antibodies can develop immune-related adverse events due to activation of the immune system. Case presentation: We report a case of a patient who received pembrolizumab and presented with cardiac tamponade. Despite pericardial drainage, she persisted with refractory arterial hypotension due to secondary adrenal insufficiency. After initiating corticosteroid therapy, the patient recovered successfully. Discussion: The association of pericarditis, hypophysitis and thyroid dysfunction support the diagnosis of a life-threatening immune-related adverse event due to pembrolizumab. In case of immune-related adverse events secondary to anti-PD-1 monoclonal antibodies, corticosteroid therapy should be promptly initiated in order to avoid major complications.